Macroscopic Displacement Reaction of Copper Sulfide in Lithium Solid‐State Batteries. Issue 41 (28th September 2020) - Santhosha, Aggunda L.; Nazer, Nazia; Koerver, Raimund; Randau, Simon; Richter, Felix H.; Weber, Dominik A.; Kulisch, Joern; Adermann, Torben; Janek, Jürgen; Adelhelm, Philipp
Abstract: Copper sulfide (CuS) is an attractive electrode material for batteries, thanks to its intrinsic mixed conductivity, ductility and high theoretical specific capacity of 560 mAh g −1 . Here, CuS is studied as cathode material in lithium solid‐state batteries with an areal loading of 8.9 mg cm −2 that theoretically corresponds to 4.9 mAh cm −2 . The configuration of the cell is LiLi3 PS4 [CuS (70 wt%) + Li3 PS4 (30 wt%)]. No conductive additive is used. CuS undergoes a displacement reaction with lithium, leading to macroscopic phase separation between the discharge products Cu and Li2 S. In particular, Cu forms a network of micrometer‐sized, well‐crystallized particles that seems to percolate through the electrode. The formed copper is visible to the naked eye. The initial specific discharge capacity at 0.1 C is 498 mAh g(CuS) −1, i.e., 84% of its theoretical value. The initial Coulomb efficiency (ICE) reaches 95%, which is higher compared to standard carbonate‐based liquid electrolytes for the same cell chemistry (≈70%). After 100 cycles, the specific capacity reaches 310 mAh g(CuS) −1 . With the current composition, the cell provides 58.2 Wh kg −1 at a power density of 7 W kg −1, which is superior compared to other transition metal sulfide cathodes. Abstract : Copper sulfide (CuS) is an attractive electrode material for solid‐state lithium batteries. During discharge, it undergoes a displacement reaction with lithium leading to a network of micrometer‐sized copper crystals. Despite the volume expansion during discharge, the cell cycles over many cycles reaching 310 mAh g(CuS) −1 after 100 cycles.